Christmas Time at Frances Kamp's Home in San Mateo - Watkins, Howard::::::::: (1985)
Howard Watkins, Marketa Smith, Adam Watkins, Juanita Smith, Christine Watkins and Robin Watkins on lap of Frances Kamp